Evidence of association of macrophage migration inhibitory factor gene polymorphisms with systemic lupus erythematosus (2006)
The aim of this study was to evaluate the potential association of functional polymorphisms of macrophage migration inhibitory factor with systemic lupus erythematosus. Our study includes 711 systemic lupus erythematosus (SLE) patients and 755 healthy controls. We genotyped the migration inhibitory factor (MIF) -173G/C using a polymerase chain reaction (PCR) system with predeveloped TaqMan allelic discrimination assay and the MIF -794 CATTn microsatellite polymorphism using a PCR-fluorescent method. A statistically significant difference in the distribution of the MIF -173*C allele between SLE patients and controls (P=0.004, OR=1.34, 95% CI=1.05-1.27) was observed. In addition, the frequency of the MIF -173* C/C genotype was higher in SLE patient (P=0.002, OR 2.58, 95% CI 1.32-5.10). No differences in the distribution of CATTn were found. However, the haplotypes analyses showed that only the CATT7-MIF -173* C haplotype was associated with a higher susceptibility to SLE (P=0.001, OR 1.84, 95% CI 1.35-2.79). No association with clinical features was detected in any case. These results suggest that both, MIF -173*C allele and CATT7-MIF -173*C haplotype, confer susceptibility to SLE in our population. © 2006 Nature Publishing Group. All rights reserved.